Morphemic Reduplications in Geguritan - Susetyaningsih, Ririn; Handayani, Wiwik Retno (Universitas Dian Nuswantoro, 2023)
The research aims at investigating morphemic reduplication in terms of its kinds and meanings in Javanese poetry, widely known as geguritan. This descriptive qualitative study obtained the data from an anthology of geguritans entitled Cathetan Kanggo Lintang by Irul S. Budianto. An interpretative method was conducted after the data were noted, listed, verified, and classified based on the kinds of meanings of reduplication as proposed by Wijana. The research findings show that the kinds of reduplication found in the geguritans can be classified into four: full reduplication, reduplication with sound modification, partial initial syllabic reduplication, and reduplication combined with affixation. In addition, only nine out of 12 categories of the meanings of reduplication were found in the data. The absence of the three categories is due to the difference between the language style used in geguritan and the language used in daily conversation.